Visual Function Improvement After Optic Nerve Sheath Fenestration in Osteopetrosis Patients with Optic Canal Stenosis: A Report of Two Cases. (4th May 2018) - Alshowaeir, Daniah; Ajlan, Abdulrazag; Hussain, Sajjad; Alsuhaibani, Adel
ABSTRACT: The outcome of two patients with visual loss from osteopetrosis who underwent an optic nerve sheath fenestration (ONSF) is reported. A 20-year-old male and 26-year-old female with osteopetrosis had optic nerve edema. Computed tomography and magnetic resonance imaging demonstrated optic canals stenosis. Both patients underwent unilateral ONSF. After ONSF, the patients experienced improvement in visual acuity and optic nerve appearance. Therefore, when papilledema is recognized in osteopetrosis patients, it may be reasonable to start with an ONSF even if the optic canal seems to be stenotic because of the lower morbidity that is associated with this procedure compared with other surgical options.